Use of a point-of-care beta-hydroxybutyrate sensor for detection of ketonemia in dogs - Henderson, Debra W. (Canadian Veterinary Medical Association, 2010)
The urine test strip is the most common test used to detect ketones in veterinary patients, but it can underestimate the degree of ketonuria and hence, ketonemia. Additionally, adequate urine samples for analysis may be difficult to obtain from dehydrated animals. The standard method used to detect and monitor ketonemia in human medicine is measurement of serum or whole blood beta-hydroxybutyrate (βHOB). A point-of-care (POC) analyzer has been validated for this purpose in humans. This study compared the accuracy of the POC device to an enzymatic reaction laboratory method for measurement of βHOB in dogs. Although the POC sensor tended to overestimate βHOB concentrations, there was good correlation (R(2) = 0.96) and good agreement between the 2 methods with a bias +/− precision of 0.0860 +/− 0.3410 mmol/L βHOB. The POC βHOB sensor can be useful for assessing ketonemia in dogs.